(untitled) (Journal of Fatima Jinnah Medical University, 2021)
Background: The study was done to identify the maternal and fetal factors contributing to neonatal outcome and to evaluate the correlation between risk factors and adverse neonatal outcome. Subjects and methods: This prospective observational study was conducted on 126 mothers and their neonates fulfilling the selection criteria at Al-Tibri Medical College and Hospital. A self-designed Performa was used to enter data of subjects. Sick neonates were referred to neonatal intensive care unit for admission and management. The results were analyzed by using SPSS version 22. A p-values <0.05 was considered as significant. Results: Out of 126 enrolled subjects, 81% mothers were multigravidas, 31% were unbooked, 13.5% had gestational comorbidities, 15% were drug addict, 2% were Hepatitis B positive. 22.2% underwent emergency LSCS while 31.7% delivered babies by elective LSCS. Regarding fetal factors contributing to sick babies, IUGR (20%), twin fetuses (15.4%), prematurity (47.7%) were significant. 65 were sick babies. Adverse neonatal outcomes observed were prematurity in 25.4%, IUGR in 11.1%, NICU admission in 33.3%, and neonatal death in 2%. Risk factors associated with adverse neonatal outcomes were positive maternal drug addiction (p-value = 0.028), preterm delivery (p-value<0.001), NICU admission (p-value<0.001) and low birth weight (p-value <0.001). Conclusion: Compromised maternal antenatal care has profound deleterious effect on fetus and neonate. Obstetricians, perinatologists and neonatologists need to work in concord to improve maternal antenatal care hence improving neonatal outcome. In our study adverse neonatal outcome was associated with unbooked cases, delivery by EmLSCS, addicted mother, preterm delivery, LBW and neonates requiring NICU admission.